Letální syndromy v pediatrii - tři příběhy trizomie 18 - Ducháčová, Michaela; Pavlíček, Jan; Pavlíčková, Eva; Nowaková, Markéta; Trávníček, Bořek; Kuzníková, Iva; Broďáková, Tereza (Pediatrie pro praxi, 2023)
Edwards syndrome is a significant genetic abnormality with an unfavorable prognosis. It has a high rate of prenatal detection, which significantly affects its occurrence in the pediatric population. Postnatally, the dominant organ pathology is heart defects, clinically these patients always present with psychomotor impairment and failure to thrive. Despite the high percentage of early lethality, some patients may live longer than one year, and it is, therefore, to set up complex care for them. This care is available, including the management of organ pathologies. Complex or palliative care concepts are of considerable benefit in these children.
Keywords: indukovaný potrat; Female; syndrom trizomie 18; Infant Death; novorozenec; Heart Defects, Congenital; Postnatal Care; ženské pohlaví; smrt kojence; prenatální diagnóza; lidé; Abortion, Induced; Infant, Newborn; Prenatal Diagnosis; mnohočetné abnormality; postnatální péče; Abnormalities, Multiple; vrozené srdeční vady; Trisomy 18 Syndrome; Humans